Local governance in developing countries (The World Bank, 2006)
Shah brings together 12 essays that examine the role of local governments in developing countries, as well as a comparative institutional framework for governance. In addition, the essays follow the history of local governance, discuss alternative models, and offer case studies of 10 countries--South Africa, Uganda, China, India, Indonesia, Kazakhstan, Poland, Argentina, Brazil, and Chile--specifically looking at their organization and finance. These include country briefs prepared for World Bank Institute learning programs by authors from around the world. The volume aims to "advance the World Bank Institute agenda on knowledge sharing and learning from cross-country experiences in reforming public governance" and is meant for public officials, development practitioners, and students, and to strengthen governments and improve social outcomes.